Evaluation Of Rodhradi Gana Of Sushruta Samhita: A Literary Review - meena, Anita; Kaushal, Kamini; Gurjar, Hemwati (International Research Journal of Ayurveda & Yoga, 2021)
Rodhradi Gana is the 6th Gana among the 37th gana described in 38th chapter- dravyasangrahniya of sutrasthan in Sushrut Samhita and includes Lodhra, Saber lodhra, Palash, Shyonak, Ashok, Bharangii, Katphal, Alvaluk, Shallaki, Jhingani, Kadamba, Shal, Kadli thirteen ingredients, which act on Yoni Roga, Kaphaj disorder and Medo dushti. Yoni roga (vaginal disorders) can be corelated with the term PCOS (poly cystic ovarian syndrome) of modern disease. These thirteen plants are work together and give enhanced effect. They are also effective individually. These plants having Madhur (sweet), Tikta (pungent), Kashaya rasa (astringent), Ruksha (rough), Laghu guna (light), Ushna Veerya, Katu Vipak And Kapha Vatghana properties, removes vagina and uterine disorders.